Reduced Genotoxicity of Gold Nanoparticles With Protein Corona in Allium cepa - Arya, Sagar S.; Rookes, James E.; Cahill, David M.; Lenka, Sangram K. (Frontiers in Bioengineering and Biotechnology, 2022)
Increased usage of gold nanoparticles (AuNPs) in biomedicine, biosensing, diagnostics and cosmetics has undoubtedly facilitated accidental and unintentional release of AuNPs into specific microenvironments. This is raising serious questions concerning adverse effects of AuNPs on off-target cells, tissues and/or organisms. Applications utilizing AuNPs will typically expose the nanoparticles to biological fluids such as cell serum and/or culture media, resulting in the formation of protein corona (PC) on the AuNPs. Evidence of PC altering the toxicological signatures of AuNPs is well studied in animal systems. In this report, we observed significant genotoxicity in Allium cepa root meristematic cells (an off-target bioindicator) treated with high concentrations (≥ 100 µg/mL) of green-synthesized vanillin capped gold nanoparticles (VAuNPs). In contrast, protein-coated VAuNPs (PC-VAuNPs) of similar concentrations had negligible genotoxic effects. This could be attributed to the change in physicochemical characteristics due to surface functionalization of proteins on VAuNPs and/or differential bioaccumulation of gold ions in root cells. High elemental gold accumulation was evident from µ-XRF mapping in VAuNPs-treated roots compared to treatment with PC-VAuNPs. These data infer that the toxicological signatures of AuNPs are influenced by the biological route that they follow to reach off-target organisms such as plants. Hence, the current findings highlight the genotoxic risk associated with AuNPs, which, due to the enhanced utility, are emerging as new pollutants. As conflicting observations on the toxicity of green-synthesized AuNPs are increasingly reported, we recommend that detailed studies are required to investigate the changes in the toxicological signatures of AuNPs, particularly before and after their interaction with biological media and systems.